1992
DOI: 10.1152/jappl.1992.73.6.2559
|View full text |Cite
|
Sign up to set email alerts
|

Vascular effects of platelet-activating factor in lambs: role of cyclo- and lipoxygenase

Abstract: In adult sheep, platelet-activating factor (PAF) effects include systemic hypotension and pulmonary hypertension. To identify developmental differences in vascular responses to PAF, we studied the effects of C18- and C16-PAF in 49 +/- 2- (SE) day-old lambs. Responses of upstream (arteries and microvessels) and venous segments of the lung to C18-PAF were determined both in vivo and in isolated lungs. In isolated lungs, the role of eicosanoids in PAF effects was also determined. In vivo, both C18- and C16-PAF ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…In fetal pulmonary circulation, vasoconstrictors such as PAF and thromboxane A 2 (Toga et al, 1992;Argiolas et al, 1995;Ibe et al, 1998) maintain high vasomotor tone by increasing intracellular levels of IP 3 and calcium. At birth, release of vasodilators such as cGMP and cAMP induce smooth muscle relaxation by acting through their respective protein kinases, PKG and PKA (Dhanakoti et al, 2000;Abdel-Latif, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fetal pulmonary circulation, vasoconstrictors such as PAF and thromboxane A 2 (Toga et al, 1992;Argiolas et al, 1995;Ibe et al, 1998) maintain high vasomotor tone by increasing intracellular levels of IP 3 and calcium. At birth, release of vasodilators such as cGMP and cAMP induce smooth muscle relaxation by acting through their respective protein kinases, PKG and PKA (Dhanakoti et al, 2000;Abdel-Latif, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…All studies were done with smooth muscle cells harvested from intrapulmonary veins of term fetal lambs, because they exhibit more PAF binding than cells from arteries (Ibe et al, 2005). Also, we have previously reported that in the fetus, pulmonary veins often demonstrate significantly greater vasoactivity than pulmonary arteries, and veins contribute a significant fraction to pulmonary vascular resistance in utero (Kääpä et al, 1991;Toga et al, 1992).…”
Section: Preparation Of Pulmonary Vascular Smooth Muscle Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, besides bronchoconstriction [22], PAF produces many effects that may contribute to oedema formation, for example, hydrostatic mechanisms, such as activation of neutrophils [23,24], pulmonary vasoconstriction [25,26] and platelet aggregation [24]. Although these factors may aggravate pulmonary oedema, the major factor in PAF-induced oedema formation appears to be increased vascular permeability.…”
Section: Increased Cytosolic Camentioning
confidence: 99%
“…They have been implicated as mediators in asthma and other types of allergic reaction [1]. Recent reports have also shown that 5LO is involved in tumour cell proliferation [2][3][4][5][6][7] and is related to primary pulmonary hypertension [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%